The trajectories of sleep disturbances in Rett syndrome - Wong, K.; Leonard, H.; Jacoby, P.; Ellaway, C.; Downs, Jennepher (Blackwell Publishing Ltd, 2015)
Rett syndrome is a rare neurodevelopmental disorder usually affecting females, and is associated with a mutation in the MECP2 gene. Sleep problems occur commonly and we investigated the trajectories and influences of age, mutation and treatments. Data were collected at six time points over 12 years from 320 families registered with the Australian Rett Syndrome Database. Regression analysis was used to investigate relationships between sleep disturbances, age, mutation type and use of treatment, and latent class growth analysis was performed to identify sleep problem phenotypes and model the effect of mutation type. The age range of subjects was 2.0–35.8 years. The study showed that sleep problems occurred in more than 80% of individuals and the prevalence decreased with age. Night laughing and night screaming occurred in 77 and 49%, respectively, when younger. Those with a large deletion had a higher prevalence of night laughing, which often occurred frequently. Treatment was associated with a 1.7% reduction in risk of further sleep problems. High and low baseline prevalence groups were identified. Approximately three-quarters of girls and women with sleep disturbances were in the high baseline group and problems persisted into adulthood. Conversely, 57% with night laughing and 42% with night screaming in the high baseline group exhibited mild improvement over time. Mutation type was not found to be a significant predictor of group membership. In conclusion, the evolution of sleep problems differed between subgroups of girls and women with Rett syndrome, in part explained by age and genotype. Treatment was not associated with improvement in sleep problems.